Brain endurance training modulates structure-function coupling and enhances soccer-specific performance: a multimodal MRI study - Liu, J.; Zhou, T.; Che, J.; Zhu, Y.; Liu, Q. (Scandinavian Journal of Medicine & Science in Sports, 2026)
This study investigated whether a six-week brain endurance training (BET) intervention could enhance soccer-specific performance and induce neural adaptations in structure-function coupling (SC-FC coupling) in sub-elite male soccer players. Seventy athletes competing in the regional first division and engaged in structured training 5-6 times per week were randomly assigned to a BET group (n = 35) or a control group (n = 35). Both groups continued regular field training, while the BET group additionally completed 24 cognitive sessions combining Stroop and dual n-back tasks. Resting-state fMRI and diffusion-weighted imaging were acquired before and after the intervention to assess SC-FC coupling across 246 brain regions using a multivariate prediction framework. Soccer performance tests included passing, shooting, agility, sprint, and aerobic capacity assessments. Compared with controls, BET participants demonstrated significant group × time interactions in passing accuracy, shooting precision, reactive agility, and sprint performance (all p < 0.05, n2p = 0.06-0.07). Specifically, LSPT completion time improved by 3.7%, LSST precision increased by 11.2%, and directional sprint times decreased by 5.1% following BET, with no change in the control group. Maximum running speed during the 30-15 Intermittent Fitness Test increased by 2.9% (p = 0.043, n2p = 0.07), whereas heart rate and blood lactate remained stable. MRI analyses revealed increased SC-FC coupling within executive and motor-related regions (e.g., DLPFC, IPL, caudate, Crus I) and decreased coupling within default mode and association areas (e.g., angular gyrus, pSTG; all p < 0.05, FDR-corrected). These coupling changes were significantly correlated with behavioral improvements, indicating that BET enhanced the neural efficiency of executive-motor networks. Overall, BET drives targeted neuroplasticity by strengthening the alignment between structural and functional brain systems that support attention, motor control, and fatigue regulation, translating into measurable gains in soccer-specific performance.